(untitled) (International Journal of Food and Nutritional Sciences, 2022)
This paper presents a novel approach to improve train ticket purchase services by integrating a train ticket trading system with an Automated Teller Machine (ATM) in an embedded mode. By combining an IC card recognition module and the ATM, the system achieves real-name system information checking, ensuring a secure and reliable user experience. Furthermore, the integration of a payment module with the ATM enables various payment modes, including cash and Unionpay transfer.